2020
DOI: 10.3390/ijerph17082887
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Uptake of Lettuce and Ryegrass from Urban Waste Composts

Abstract: Interest in using urban waste composts as amendments in urban agriculture is growing nowadays. However, concerns about the potential transference of pollutants present in urban waste to the food chain are very relevant when they are recycled for food or animal feed production. Thus, for the safe use of urban waste composts, it has to be assured that no risk of metal transference to plants from compost exists. In this work, the transference of heavy metals from urban waste composts to plants has been studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…Nevertheless, only the Cd content exceeded the standard levels. However, many works found Cd-soluble concentrations in leachate below the detectable rates and an increment of the soluble fractions of Zn and Ni [65]. Cu and Zn availability is increased with MSW [66], as well as it has been reported for landfill sites [67].…”
Section: Micronutrients and Trace Elements From Mswmentioning
confidence: 91%
“…Nevertheless, only the Cd content exceeded the standard levels. However, many works found Cd-soluble concentrations in leachate below the detectable rates and an increment of the soluble fractions of Zn and Ni [65]. Cu and Zn availability is increased with MSW [66], as well as it has been reported for landfill sites [67].…”
Section: Micronutrients and Trace Elements From Mswmentioning
confidence: 91%
“…El compost es el producto obtenido del proceso de biodegradación de materia orgánica en estado sólido en condiciones aerobias (Yuksel, 2015). Así mismo, el compost producido en base a los residuos sólidos orgánicos municipales (RSOM), puede ser una oportunidad para el desarrollo de ciudades verdes en las áreas urbanas en crecimiento (Fetene et al, 2018), así como un valioso recurso para la agricultura y remediación de suelos, cuya producción contribuye al desarrollo sustentable a través del reciclado de materia orgánica y nutrientes (Paradelo et al, 2020). El compost maduro producido por compostaje aeróbico podría mejorar la fertilidad del suelo y aumentar el rendimiento en los cultivos, dependiendo de la fuente de residuos utilizados (RSU, agroindustriales, pecuarios entre otros) (Cui et al, 2021).Así mismo, en su composición presenta materia orgánica soluble derivada del proceso oxidativo biológico; por ello las sustancias orgánicas biodegradables se convierten durante el proceso en productos más estables tales como los ácidos húmicos, ácidos fúlvicos, humina y microorganismos endógenos que ayudan a mejorar la calidad del suelo (Epelde et al, 2018).…”
Section: Compost De Residuos Sólidos Orgánicos Municipales/urbanosunclassified
“…Therefore, if the vegetables are contaminated, they can put a vast population at risk. Many studies reported high heavy metals [e.g., chromium (Cr), cadmium (Cd), lead (Pb), nickel (Ni), copper (Cu), zinc (Zn), iron (Fe), and manganese (Mn)] content in different vegetables (Ali and Al-Qahtani 2012; Guerra et al 2012;Huang et al 2020;Sharma et al 2007Sharma et al , 2009Manzoor et al 2018;Mishra et al 2020;Paradelo et al 2020). Mi et al (2019) have observed 35 common Chinese cabbage genotypes and studied the accumulation of five different heavy metals (Cd, Cr, Hg, Pb, and As) (Mi et al 2019).…”
Section: Introductionmentioning
confidence: 99%